Correction to “A Review of Basketball Shooting Analysis Based on Artificial Intelligence” - Wenlin Yan; Xianxin Jiang; Ping Liu (IEEE Access, 2024)
In the above article [1], the Acknowledgment section was missing. This section should contain the sentence: “This work was supported by the Science and Technology School-Strengthen Project of CUPES, No.155223016.”